Strategi Ketidaksantunan dalam Film “Siap, Gan!” - Putri, Nabila Destya; Pribalisty, Nesa Aureola; Hidayati, Mardliyyah; Jaya, Mido Mashela; Lukman, Lukman; Nugroho, Miftah (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The politeness of speech acts can be influenced by certain sociological factors, for example, relative power, social distance, and the presence of elements of coercion. In its development, politeness in speech acts also develops in its opposite form, namely impoliteness. The focus of the study in this research is the language impoliteness strategy in the film "Siap, Gan!" which appears as a reflection of differences in social levels by focusing discussion on the five strategies of impoliteness according to Culpeper's theory. This research aims to describe impolite language strategies in films. The type of research used in this research is qualitative and the data provision technique used in this research is observation/observation techniques. Observation techniques are carried out without involving what is being observed. The data source for this research comes from a video film entitled "Siap, Gan!" obtained on the YouTube channel. The analysis carried out in this research uses contextual analysis. Contextual analysis involves several elements, namely identifying speakers and speech partners, observing the background or causes of the speech, and the goals to be achieved through the speech data analysis, it is known what types of language impoliteness appear in the film "Siap, Gan!" namely bald on record impoliteness, positive impoliteness, and negative impoliteness. The most frequently used strategy is negative impoliteness. This proves the impoliteness in the film "Siap, Gan!" This tends to be used to attack the speaker's negative face. Some of the data findings indicate that several forms of words that are personally offensive to the speaker due to different social strata are also found to be presented as directly impolite with harsh, insulting, degrading, and critical language.